2021
DOI: 10.1186/s13068-021-01901-5
|View full text |Cite
|
Sign up to set email alerts
|

Acetate as substrate for l-malic acid production with Aspergillus oryzae DSM 1863

Abstract: Background Microbial malic acid production is currently not able to compete economically with well-established chemical processes using fossil resources. The utilization of inexpensive biomass-based substrates containing acetate could decrease production costs and promote the development of microbial processes. Acetate is a by-product in lignocellulosic hydrolysates and fast pyrolysis products or can be synthesized by acetogens during syngas fermentation. For the fermentation of these substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…The concentration was converted into g/L assuming the density of water [ 2 ]. The only exception was acetate, for which, according to the results of Kövilein et al [ 42 ], no growth limit was determined so far b GC/MS analysis performed by Thünen Institute of Wood Research in Hamburg for PAC that was neither pH adjusted nor filtered…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration was converted into g/L assuming the density of water [ 2 ]. The only exception was acetate, for which, according to the results of Kövilein et al [ 42 ], no growth limit was determined so far b GC/MS analysis performed by Thünen Institute of Wood Research in Hamburg for PAC that was neither pH adjusted nor filtered…”
Section: Resultsmentioning
confidence: 99%
“…The concentration was converted into g/L assuming the density of water [ 2 ]. The only exception was acetate, for which, according to the results of Kövilein et al [ 42 ], no growth limit was determined so far…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that A. oryzae DSM 1863 is a promising natural l -malic acid producer with a wide substrate range ( Ochsenreither et al, 2014 ; Dörsam et al, 2017 ; Kövilein et al, 2021 ). For further process understanding and optimization of malic acid production, we compared the three fermentation strategies, batch, fed-batch, and repeated-batch, in parallel shake flask cultivations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the additional calcium and CO 2 supply via calcium carbonate might also have a positive effect on the malic acid production. In a study that investigated the role of calcium carbonate in the l -malic acid production with A. oryzae from acetate, the authors concluded that the formation of Ca-malate might have been the main function of calcium carbonate ( Kövilein et al, 2021 ), whereas its role as a CO 2 donor and buffering agent was assumed to be less important. However, for malic acid production on glucose, all functions of calcium carbonate could be beneficial.…”
Section: Discussionmentioning
confidence: 99%